Salinomycin in cancer: a new mission for an old agent - Naujokat, Cord; Fuchs, Dominik; Opelz, Gerhard (Molecular medicine reports, 2010)
Salinomycin is a monocarboxylic polyether ionophore isolated from Streptomyces albus that has been used for more than 30 years as an agricultural antibiotic to prevent coccidiosis in poultry and to improve nutrient absorption and feed efficiency in ruminants and swine. As a inonophore with strict selectivety for alkali ions and a strong preference for potassium, salinomycin interferes with transmembrane potassium potential and promotes the efflux of K+ ions from mitochondria and cytoplasm. Salinomycin has recently been shown to kill human cancer stem cells and to inhibit breast cancer growth and metastasis in mice. Salinomycin is also able to induce massive apoptosis in human cancer cells of different origins that display multiple mechanisms of drug and apoptosis resistance. Salinomycin activates an unconventional pathway of apoptosis in human cancer cells that may contribute to the breakdown of apoptosis resistance. The ability of salinomycin to effectively kill both cancer stem cells and apoptosis-resistant cancer cells may define the compound as a novel and effective anticancer agent.
Gesehen am 05.05.2023